Strategi Pemasaran Bank Aman Syariah Dalam Menarik Minat Nasabah Tabungan Haji Mabrur (Tajimabrur) - Triwibowo, Ananto; Baidhowi, Muhammad Mujib; Nita, Veni Alvia (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study was to analyze the marketing strategy implemented by Bank Aman Syariah Sekampung on haj savings products in attracting customer interest. The type of research used is field research which is descriptive qualitative. The data sources used are primary data sources and secondary data sources. For data collection using interview techniques and documentation. The data analysis technique used in this study is through qualitative data analysis. The results of this study indicate that based on the 7p marketing strategy that has been implemented by Bank Aman Syariah Sekampung there are effective strategies in attracting customer interest, namely product, price, place, people and process strategies. Meanwhile, strategies that are less effective in attracting customer interest in haj savings products are promotional strategies and physical evidence. In the promotion strategy, the promotion carried out by Bank Aman Syariah Sekampung is not optimal, namely for the media there is no special brochure for Hajj savings and the lack of active promotion carried out through social media such as Instagram and Facebook. The physical evidence strategy is less effective because in the last 5 years there have been no customers who have performed the pilgrimage using the Hajj savings product of Bank Aman Syariah, this has made the public less confident because there is no evidence considering the physical evidence shows how the quality of a product..